A young infant with complete androgen insensitivity syndrome (BIRDEM Medical Journal, 2021)
Complete androgen insensitivity syndrome (CAIS) is a rare X-linked recessive disorder resulting from maternally inherited or de novo mutations involving the androgen receptor (AR) gene. The AR is a vital steroid hormone receptor that has a critical role in male sexual differentiation and development and preservation of the male phenotype. The diagnosis of CAIS is based on the presence of female external genitalia in an individual with 46, XY karyotype having normally developed but undescended testes and target tissue unresponsiveness to androgen. Our case presented at the age of 2 months with asymmetric labia majora with bilateral labial mass. Ultrasonography revealed absence of female internal genital organs and presence of testes at labial folds. The child was found to have 46, XY karyotype.BIRDEM Med J 2022; 12(1): 74-77